Cult of the goddess - Sengupta, Arputha Rani; Mishra, R. C.; Chakravarty, Kalyan Kumar (D. K. Printworld, Publishers of Indian Traditions, 2015)
Papers presented at a national seminar held at New Delhi in 2005